Developing health communication messaging for a social marketing campaign to reduce tobacco use in pregnancy among Alaska native women. (2nd October 2018) - Patten, Christi A.; Lando, Harry; Resnicow, Kenneth; Decker, Paul A.; Smith, Christina M.; Hanza, Marcelo M.; Burhansstipanov, Linda; Scott, Matthew
ABSTRACT: Background: Despite the high prevalence of tobacco use during pregnancy among Alaska Native and American Indian (AI/AN) women, few efforts have focused on developing tobacco cessation interventions for this group. This paper describes development of messaging for a social media campaign targeting the entire community to reduce tobacco use in pregnancy (cigarette smoking and smokeless tobacco use including a homemade product known as Iqmik) among AN women, as part of a multi-component intervention. Method: The study (clinical trial registration #NCT02083081) used mixed methods with two rounds of assessments to develop and refine culturally relevant message appeals. Round 1 used qualitative focus groups and individual interviews ( n  = 60), and Round 2 used quantitative survey interviews ( n  = 52). Each round purposively sampled adult AN pregnant women, family/friends, and Elders in Western Alaska, and included tobacco users and non-users. Round 1 also assessed reasons for tobacco use in pregnancy. Results: Qualitative findings generally converged with quantitative results to indicate that many participants preferred factual, loss-framed, visual concepts on how maternal tobacco use harms the fetus, newborn, and child in contrast to spiritual or emotional appeals, or gain-framed messaging. Stress was indicated as a major reason for tobacco use in pregnancy and strategies to manage stress along with other health pregnancy targets (e.g. prenatal care) were suggested. Conclusions: This preliminary study suggests campaign messages targeting the entire community to reduce tobacco use in pregnancy among rural AN women should include factual messaging for being tobacco-free as well as focus on reducing stress and other healthy pregnancy targets.